Bedeutung der Energieeffizienz für die Energiewende - Franziska Löw (Wirtschaftsdienst, 2016)
Das Erneuerbare-Energien-Gesetz sieht für Endverbraucher einen Strompreis mit einem relativ großen Anteil aus der Umlage für Strom aus erneuerbaren Energien vor. Das Gesetz enthält jedoch Ausnahmeregelungen für stromintensive Industrieunternehmen, um deren internationale Wettbewerbsfähigkeit nicht zu gefährden. Durch diesen Mechanismus besteht für Unternehmen kein Anreiz, die Energieeffizienz zu verbessern, und damit auch kein Anreiz, die deutsche Energiewende effizient zu gestalten. – – The increase of the share of renewables in Germany's energy mix will not emerge from market mechanisms, and hence the costs of externalities have to be distributed among market participants. In order to preserve their competitiveness, energy intensive industries in Germany are exempt from these costs, which in turn leads to a surplus load for remaining consumers. In the context of an efficient energy system transformation, this policy measure is questionable. Even if high electricity prices lead to higher input costs in the short term, an exception for energy intensive industries cannot be justified. On the contrary, this mechanism impedes incentives for investments in energy efficiency and therefore reduces competitiveness in the long term.
Keywords: O14; Q48; Q52; 330